2012
DOI: 10.1016/j.febslet.2012.03.044
|View full text |Cite
|
Sign up to set email alerts
|

The effects of modifying RhoA and Rac1 activities on heterotypic contact inhibition of locomotion

Abstract: a b s t r a c tContact inhibition of locomotion (CIL) occurs when a cell ceases moving in the same direction following contact with another cell. Homotypic and heterotypic CIL occur between cells of the same and different types, respectively. Using Abercrombie's confronted explants assay we studied the effect of changing Rac1 or RhoA activities on heterotypic CIL between NIH3T3 and chicken heart fibroblasts. Both dominant active (L61) and dominant negative (N17) Rac1 expressed in NIH3T3 cells resulted in loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…When fibroblasts with normal motility collide, they undergo temporary paralysis of movement and then divert their paths to avoid contact in a phenomenon known as contact inhibition of locomotion, which was first described by Michael Abercrombie and Joan Heaysman in the early 1950s [90,91]. The cell overlap shown by IRM here indicates that ROCK inhibition causes a release from contact inhibition of locomotion, as reported before [92][93][94], and reviewed by Mayor and Carmona-Fontaine [95]. A consequence of contact inhibition of locomotion is that sparse cells will translocate faster than more numerous cells due to a lesser number of collisions [90].…”
Section: Functional Consequences Of Irs-1 Inhibitionsupporting
confidence: 66%
“…When fibroblasts with normal motility collide, they undergo temporary paralysis of movement and then divert their paths to avoid contact in a phenomenon known as contact inhibition of locomotion, which was first described by Michael Abercrombie and Joan Heaysman in the early 1950s [90,91]. The cell overlap shown by IRM here indicates that ROCK inhibition causes a release from contact inhibition of locomotion, as reported before [92][93][94], and reviewed by Mayor and Carmona-Fontaine [95]. A consequence of contact inhibition of locomotion is that sparse cells will translocate faster than more numerous cells due to a lesser number of collisions [90].…”
Section: Functional Consequences Of Irs-1 Inhibitionsupporting
confidence: 66%
“…EphA receptor activation has been shown to lead to cell retraction via RhoA in several cell types (Astin et al, 2010; Lawrenson et al, 2002; Ogita et al, 2003; Shamah et al, 2001; Wahl et al, 2000) and RhoA has been implicated in CIL (Anear and Parish, 2012; Carmona-Fontaine et al, 2008; Kadir et al, 2011; Theveneau et al, 2010). However, the functional requirement for RhoA in prostate cancer contact repulsion has not been shown.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that Rho GTPases play key roles during CIL (Anear and Parish, 2012; Astin et al, 2010; Carmona-Fontaine et al, 2008; Kadir et al, 2011; Theveneau et al, 2010). Rho GTPases are key regulators of the actin and microtubule cytoskeleton and cell polarity, and may regulate all of the key repulsion steps during CIL.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recognition of CIL over half a century ago, methods for its in vitro study have remained largely unchanged, and involve either placing two tissue explants in close proximity in culture, or directly observing rare, serendipitous collisions between dissociated cells [1,3,4,19,20]. As a result, these methods have limited quantitative insight into CIL.…”
Section: Introductionmentioning
confidence: 99%